Experimental investigations of concrete-filled steel tubular columns confined with high-strength steel wire. Issue 13 (October 2019) - Wei, Yang; Cheng, Xunyu; Wu, Gang; Duan, Maojun; Wang, Libin
The use of high-strength steel wires is proposed to provide external confinement for concrete-filled steel tubular columns. This article presents an experimental study on high-strength steel-wire-confined concrete-filled steel tubular columns with various high-strength steel wire spacings and steel tube thicknesses and diameters. As observed from the experimental results, high-strength steel wires can effectively constrain and delay the local buckling of the steel tube in concrete-filled steel tubular columns. As a result, the load-carrying capacity and the post-peak stiffness of concrete-filled steel tubular columns are significantly increased by the high-strength steel wire confinement. When the spacing of the high-strength steel wires decreases, the load–axial strain response can evolve from a softening behavior to a hardening behavior for the concrete-filled steel tubular columns. Moreover, theoretical models were developed to predict the load-carrying capacity of the externally confined concrete-filled steel tubular columns, taking into account the mechanical mechanism and the triaxial stress state of the inner concrete. The analytical results are generally in reasonable agreement with the experimental results.